Unusual rearrangements in activated indoles: Synthesis of indoloquinolines, dibenzonaphthyridines and indolobenzodiazepines. Issue 33 (14th August 2020) - Qu, Ji; Bhadbhade, Mohan; Dobrowolski, Jeremy C.; Kumar, Naresh; Black, David StC.
Abstract: Reaction of 2-arylindoles with 2-acetamidobenzyl chloride gave 3-alkylated indoles rather than those substituted at nitrogen. Similar reactions with 3-arylindoles gave reduced indoloquinolines, and a 2, 3-diphenylindole gave a 3-alkylated indole. On reaction with phosphoryl chloride, the amidobenzyl-indoles undergo rearrangement to benzonaphthyridines. Similarly, the indoloquinolines undergo rearrangement to benzodiazepino-indoles. Graphical abstract: Image 1 Highlights: Methoxy groups activate indoles to undergo rearrangements leading to new structures. Hetero-Diels-Alder cycloaddition occurs across C2–C3 bond of activated indoles. Activated 3-substituted indoles react to give new indoloquinoline derivatives. Generation of iminium cations causes expansion of the indole to a quinoline. Syntheses of dibenzonaphthyridines and diazepinoindoles from iminium ion reactivity.